ORGANIZATIONAL CULTURE - DECISIVE FACTOR FOR SAFETY AND HEALTH AT WORK IN CONSTRUCTION COMPANIES - Melo, Maria Bernadete Fernandes Vieira de (2012)
The solution to the problems associated with the precarious conditions of work on building sites exists and it is practicable, although the unsafety is still a constant in the majority of these places. Even the companies that apply safety at work in its productive process do it in a punctual and instantaneous manner, without planning and without having an established politics of Safety and Health at Work. This article does a reflection about this question emphasizing that safety and health at work are linked to factors such as beliefs and values of the people who are responsible for decision making in companies. These factors are the essence of a companyâs culture. Trough a case study, it is proved that the organizational culture is a determining factor to the development of the management system of Safety and Health at Work in the building companies.